Russian Modernization: The Goal-setting in Politics - Boris Igorevich Makarenko (Сравнительная политика, 2015)
Academic discussion on the essence and directions of Russian modernization immediately followed the official declaration of a respective policy by Russian President Dmitry Medvedev. The article analyzes not only the existing approaches towards modernization in Russia, but also historical examples of political and economic modernizations and their interdependence. The author enumerates a number of problems and goals of modernization taking into account possible risks and obstacles to the process. A “reset” of the mechanism of political competitiveness and democratization is a key objective.